2006
DOI: 10.1108/00400910610692967
|View full text |Cite
|
Sign up to set email alerts
|

Communication apprehension and maths anxiety as barriers to communication and numeracy skills development in accounting and business education

Abstract: PRACTICAL IMPLICATIONS: Where high levels of communication apprehension in accounting students and maths anxiety in business studies students are shown to exist consideration must be given to relevant curriculum design and delivery, and the use of techniques designed to reduce apprehension/anxiety in the students concerned.Because the apprehension/anxiety is present on entry to Higher Education it may be that specific courses appear to be recruiting students whose perception of their 3 longer term vocational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…They also noted that secondary school students' quantitative skill might be a sign of success in university education. Later research by Chudi (2013), Joyce et al (2006), Pozo and Stull (2006), and Wilder (2020) indicated that a link exists amid students' accomplishment in completing economic subjects and mathematics/quantitative proficiency as well as students' numeracy abilities in learning accounting. Lacking quantitative economics skill has resulted in economics students' inability to answer SSCE questions involving calculations.…”
Section: Introductionmentioning
confidence: 99%
“…They also noted that secondary school students' quantitative skill might be a sign of success in university education. Later research by Chudi (2013), Joyce et al (2006), Pozo and Stull (2006), and Wilder (2020) indicated that a link exists amid students' accomplishment in completing economic subjects and mathematics/quantitative proficiency as well as students' numeracy abilities in learning accounting. Lacking quantitative economics skill has resulted in economics students' inability to answer SSCE questions involving calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the students admitted the weakness of understanding the basic terminologies in accounting. This also highlighted two noted factors of failure which are English comprehension (Rivero-Menendeza, Urquia-Grandeb, Lopez-Sanchez & Camacho-Minanoa, 2018;Tailab, 2013;Joyce, Hassall, Arquero-Montano & Donosoanes, 2006) and mathematical aptitude (Garkaz, Banimah & Esmaeili, 2011;Shaban, 2015). Read and study the next lessons before coming to class 21.67 18…”
Section: Resultsmentioning
confidence: 95%
“…The personal struggles of the accounting teachers still pertain to the students' weak skills. The claim is strongly anchored on the previously conducted studies identifying English (Rivero-Menendeza, Urquia-Grandeb, Lopez-Sanchez & Camacho-Minanoa, 2018;Tailab, 2013;Joyce, Hassall, Arquero-Montano & Donosoanes, 2006) and Mathematics (Garkaz, Banimah & Esmaeili, 2011;Shaban, 2015) to have significant effects on the academic performance in accounting subject. Although the methodologies and interventions are in place, the teachers need to be sensitive to the level and nature of their students.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Joyce, Hassall, Montaño & Anes, 2006; posits that previous mathematics educational background (i.e. highest previous mathematics qualification) has some significant effect on both numeracy-based attitudinal and performance-related variables.…”
Section: Educational and Family Backgroundmentioning
confidence: 99%